Huellas literarias de Lope de Vega y Calderón de la Barca en el Teatro del Siglo de Oro (Journal of the College of Basic Education, 2022)
The Golden Age is a period of flourishing in arts and literature in Spain. The last great writer of the period was Pedro Calderón de la Barca, died in 1681, and his death usually is considered the end of The Golden Age in the arts and literature. The main objective of this study presents the particularities and reforms of Lope de Vega and Calderon de la Barca in the Spanish Golden Age Theater. But before present the literary characteristics of these two authors explain in summary “Period Golden” of Spanish literature, also exposes the evolution of the theater of the Golden Age that will allow us to understand the features and styles of literary works of Spanish writers of that era, especially Lope de Vega and Calderon de la Barca represent the culmination of the Baroque theater of the Golden Age